Net worth ratio and financial instability - Toshio Watanabe (Journal of Economic Structures, 2013)
In order to better understand relationships between the real economy and financial economy, it is necessary to formulate a model of financing. New Keynesian theory emphasizes that a firm's net worth influences investment decisions and business cycles under an imperfect capital market. We have constructed a dynamic model from the standpoint of post Keynesian economics. We incorporate a dynamic equation of a firms net worth ratio and investigate financial factors, which give rise to economic instability. Our results demonstrate that a steady state can be a saddle point when the dividend rate is low and the banks lending reaction to the net worth ratio is more elastic than investment reaction. When the steady state is the saddle, the change in the basic discount rate is likely to shift the economy from an unstable path to a convergence path. Financial policy has a stabilizing effect in the long-run as well as a positive effect in the short-run.
Keywords: E12; E44; E52; 330; bank behavior; investment; unstable economy; monetary policy; Geldpolitische Transmission; Kreditgeschäft; Investition; Wirkungsanalyse; Neoklassisches Wachstumsmodell; Postkeynesianismus; Theorie